Reliability and Validity of The Visual Analogue Scale in Non-Myogenic Low Back Pain Patients - Syinta, Ahmada Norma; Komalasari, Dwi Rosella (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Non-myogenic low back pain is a health issue characterized by the primary complaint of pain in the lower back, extending from the costal area to the buttocks, typically radiating down to the legs. LBP can lead to decreased function, reduced work productivity, and high treatment costs. Non-myogenic LBP is classified into four categories based on its causes: herniated nucleus pulposus, spondylitis, spondylosis, and spondylolisthesis. Objective: To determine the reliability and validity of VAS scales in the case of intra rater and inter rater in non-myogenic LBP patients. Methods: This type of research is an observational study with the approach of methodological research and uses purposive sampling, total samples of 55 people. Visual analogue scale is used to measure the pain scale of non-myogenic lbp patients. Results: Intra- rater or test-retest VAS reliability was very high (Cronbach's alpha: 0.951, ICC: 0.951, 95% CI: 0.916-0.971, p<0.001) and inter-rater VAS reliability was very high (Cronbach's alpha: 0.959, ICC: 0.959, 95% CI: 0.929-0.976, p<0.001). The validity test seemed VAS was valid for intra-rater and inter-rater with p<0.05 and r calculated was higher than r of table (r=0.260). SEM value: 0.19 and MDC: 0.55. Conclusion: The visual analogue scale demonstrates reliability and validity for both intra-rater (test-retest) and inter-rater evaluations as a measurement tool for pain scale in patients with non-myogenic LBP.